Map showing Newfoundland railway and steamship system [June to December 1928] - Newfoundland Railway Company ([St. John's], 1928)
Black and white. Dated June to December 1928. Relief shown by hachures and spot heights. Bar scale in miles. Shows rail and steamship lines. Includes ancillary map: Newfoundland map showing Newfoundland Railway and steamship system. Includes timetables and tourist information. Semi-annual publication.